0396 A Brief, Automated Cognitive Behavioral Program Prevents Sleep Disturbance and Insomnia in Late Pregnancy: A Randomized Controlled Trial. (27th April 2018) - Bei, B; Neemia, D; Shen, L; Fulgoni, C; Blumfield, M L; Drummond, S P; Newman, L K; Manber, R
Abstract: Introduction: Sleep disturbances are common in late pregnancy, but are neglected in routine perinatal care. This randomized controlled trial aims to examine the efficacy of an automated, therapist-assisted cognitive behavioral therapy (CBT) program in addressing sleep disruption and insomnia symptoms in a community sample. Methods: First-time mothers without major medical/psychiatric conditions were recruited from Childbirth Education of an Australian public hospital. 159 women (age 33.37[3.44]) were randomized into a healthy sleep (CBT) or healthy diet control group. Participants received a 1-hr telephone session with a psychologist or dietician, and automated multimedia emails at 30 and 35 wks' gestation. Insomnia Severity Index (ISI), PROMIS Sleep Disturbance (SD), Sleep Related Impairment (SRI), Depression, and Anxiety Short Forms were administered at 28–30 wks (baseline; T1) and 36wks gestation (T2). Results: At baseline, 33.3% women reported clinically significant symptoms of insomnia (ISI>7), and 24.5% met DSM-5 criteria for Insomnia Disorder, without the duration criterion based on Duke structured interview. Mixed effects models showed overall, ISI, SD, and SRI increased significantly from T1 to T2 ( ps <.001), especially among women with low ISI at baseline. Compared to the control group, the CBT group reported significantly less increase in ISI, SD, and SRI ( ps <.01; d=0.61, 0.52, 0.53 respectively), such that changes in these measures over time in the CBT group were non-significant ( p s >.33). Effect sizes for ISI, SD, and SRI were larger among women meeting Insomnia Disorder criteria (d=0.74, 0.80, 0.38 respectively), and those with baseline ISI>7 (d=0.93, 0.90, 1.15 respectively). Changes in symptoms of depression and anxiety were not significant over time, and did not differ between groups (ps>.22). Conclusion: Sleep disruption and symptoms of insomnia increased with advancing gestation. A brief, automated cognitive behavioral program is efficacious in buffering against these sleep complaints during late pregnancy in a community sample of first-time mothers. The scalable nature of the program holds strong potential for dissemination and implementation in routine perinatal care. Support (If Any): Australasian Sleep Association Rob Pierce Grant in Aid, Monash University Strategic Grant Scheme.